Librarianship in times of crisis - Woodsworth, Anne (Advances in librarianship, 2011)
The field of librarianship has undergone traumatic shifts (mostly downward) due to the global financial meltdown that began in the fall of 2008. Libraries have been deeply affected by the worst recession since the Great Depression. While "Advances in Librarianship" endeavors to identify trends and innovations, the trend addressed in this volume is admittedly not a happy one. The current climate does however, present opportunities for analysis, and far reaching searches for solutions and innovations that can alleviate the challenges created by the clash of fiscal retrenchment with steadily increasing use of libraries. Therefore this volume addresses the ripple effects of the economic recession from the point of view of librarianship, the need for advocacy, and the necessity to tout the value that libraries bring to their communities. Chapters focus on identifying means to change library and library related organizations so that they focus on distinctive assets and strengths, use free or low cost resources and technologies, and position themselves to take advantage of collaborative initiatives.